(untitled) (Politeja, 2023)
REDISCOVERING JEWISH IDENTITY OF POST-WAR AUSTRIA IN ANDREAS GRUBER’S HANNA’S SLEEPING DOGS The trauma of the Holocaust, despite being dismissed for many years, has profoundly shaped the identity of successive generations of Jews. The main character of the film Hanna’s Sleeping Dogs (Hannas schlafende Hunde, 2016, Andreas Gruber) inherits the trauma of the tragic events of World War II, even though she initially remains unaware of her Jewish heritage. Upon discovering the family secret, the nine-year-old Johanna embarks on a journey to unravel her true identity. This task proves challenging in Austria, where anti-Semitism still prevailed in the 1960s, and “the myth of Hitler’s first victim” dominated the public discourse. The article aims to identify the stylistic devices employed in depicting the struggle between memory and (post)memory of tragic events. It also focuses on how Gruber narrates the story of trauma passed down from generation to generation and examines the representation of Jewish figures in his films. In addition, the film is analyzed within a sociocultural context to highlight its relevance to public discussions about Jewish identity in post-war Austria.